A SCOPING REVIEW OF FEEDING 250 MILLION INDONESIANS - Dian Kristiani Irawaty (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
Covid-19’s pandemic impacts on the Indonesians food system pose risks to human health. Little attention has been paid to food insecurity of 250 million Indonesians, resulting in a public health concern. The aim of the study is to conduct a scoping review on food security in Indonesia. Google Scholar and the Pubmed Research Documents were used to search for relevant primary research using the following terms: “food security”, “access”, “availability”, “utilisation”, “Indonesia”, and “Covid-19”. A totalled seven articles from Google Scholar and the Pubmed Research Documents were finally selected. The articles revealed three types of research approaches, those that nutritious food intake of Indonesians (n=1), those that quantified food security (n=2), and articles that addressed at least one pillar of food security during covid-19 pandemic in Indonesia (n=4). Research investigating dietary intake of carbohydrate foods is more prevalent among Indonesians, though many differences exist among participant age groups and geographical areas. Future research should include direct measurements of food intake and food security to provide a more complete picture of food security in Indonesia. Keywords: food insecurity, food availability, Indonesia.